Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina) - Janák, Jiří (Zootaxa, 2018)
The species of the genus Acylophorus Nordmann, 1837 from Madagascar and the Mascarene Islands are revised. Four already known species are redescribed and four species are described as new: A. derougemonti sp. nov., A. hova sp. nov., and A. madecassus sp. nov. from Madagascar and A. mauritianus sp. nov. from Mauritius (Mascarene Islands). Characters of all these species are described and illustrated. A key for identification is presented. The hitherto known distribution of Acylophorus in Madagascar and Mascarene Islands is discussed and mapped.